Management of Cutaneous Squamous Cell Carcinoma (Clear Cell Variant) in Bovine - A Case Report - Prajapati, Ankit S; Chauhan, Prakash M; Raval, Samir H (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Tumors of the bovine gastrointestinal tract are rare, possibly  because of the low age of the sample population (Bertone,  1990). Neoplasia in cattle carries a poor prognosis because  of early adenocarcinoma metastasis and the high fatality  of lymphosarcoma. Squamous cell carcinoma is the second  most rude type of skin cancer, with basal cell carcinoma  being the most common (Rinker et al., 2001). Squamous cell  carcinoma has been documented in bovine (Musser et al., 1993). Clear-cell squamous cell carcinoma is a rare variant  of squamous cell carcinoma, first described by Kuo (1980)  as a skin tumor. The exact etiology is unclear, but ultraviolet  radiation has been suggested as a possible cause in humans  (Lawal et al., 2013). This report documents a case of cutaneous  squamous cell carcinoma (clear cell variant) in perianal region  of a cow and its successful surgical management.
Keywords: Management; Cutaneous; Squamous